Analysis of the proverbs related to the lexemes "tongue / language" - Kurmanali, Altynshash; Suiyerkul, Botagoz; Aitmukhametova, Kuralay; Turumbetova, Zhanagul; Smanova, Bakhytgul (Opción, 2019)
The main purpose of the research is to analyze the Kazakh and Turkish proverbs related to the lexeme "tongue/language", to identify their similarities, specificities and to reveal the national and cultural characteristics of both languages. In accordance with the purpose of the research, we used the comparative and componential analysis as a tool to investigate common characteristics and distinctive features of the concept of "tongue/language". The findings of the research can be used in the elective courses like cultural linguistics, ethnolinguistics, folklore, and comparative phraseology and will serve as a material for compiling dictionaries of idioms and proverbs in lexicography